Evaluación de las prácticas verdes en restaurantes y su influencia en la intención del comportamiento del consumidor en la ciudad de Manta - Delgado Proaño, Gema Elizabeth (2019)
The purpose of this research work was to evaluate green practices in restaurants and their intention in consumer behavior in Manta city and to carry it out, the first phase corresponding to the literature review for the selection of indicators such as: sustainable purchase, efficiency in the use of water and energy, waste management, cleaning, recycling, environmental culture and emissions in the atmosphere in the variable of green practices, intention to visit, intention to spread word of mouth, intention to pay more, altruism, cost reduction, health, nutritional menu, pro-environmental activities, altruism and perceived behavior control in the intention variable of consumer behavior. These indicators were used to prepare the questionnaire for interviews with restaurant managers and consumer surveys. As another phase of the investigation, the current analysis of green practices and the intention of consumer behavior were known, starting with the selection of 20 restaurants in Manta city and then knowing the number of surveys to be carried out per restaurant through stratified sampling and a total of 272 consumers were obtained. With the information obtained, it was proceeded to tabulate data with the SPSS program and this allowed the graphic interpretation of the results and the Pearson's correlation. According to the data, it was known that there is a level of positive correlation when customers intend to behave ecologically in a restaurant that applies green practices in Manta city.